Implementation of Emotional Qur'anic Learning in Improving Memorization Ability and Love of the Qur'an in Al-Quran Hadith Learning - Rindi Putri Jiryanita; Ummidlatus Salamah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the implementation of Emotional Qur’anic Learning (EQL) in improving memorization ability and fostering students’ love for the Qur’an in the subject of Qur’an Hadith at MI Miftahussudur 02 Dagangan Parengan in the 2025/2026 academic year. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The informants consisted of the principal, teachers, and students selected using purposive sampling. Data analysis followed the model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of EQL has a positive impact on students’ memorization ability, as reflected in improved fluency, consistent revision (muroja’ah), and regular Qur’an reading habits. Additionally, students’ affective aspects developed significantly, including increased intrinsic motivation, emotional stability, and love for the Qur’an. Supporting factors include the school’s religious culture, active teacher roles, consistent learning methods, and supportive school environment. Meanwhile, inhibiting factors involve limited learning media, student boredom, individual differences in ability, and lack of parental involvement. Therefore, EQL has strong potential as an effective approach to integrate cognitive, emotional, and spiritual aspects in Qur’anic learning.